Case report: Fimosis - Amalia, Andi Zihni; Hasbi, Berry Erida; Rasyid, Mahyuddin (Indonesia Berdaya, 2024)
Phimosis is a condition where the prepuce cannot be retracted towards the glans penis, while paraphimosis is a condition where the prepuce that is retracted towards the glans penis cannot be returned to its original state. Surgical therapy for phimosis can be done with circumcision. In cases with complications, such as recurrent urinary tract infections or balloning of the prepuce during micturition, circumcision must be performed immediately regardless of the patient's age. Case Illustrations: A 6 month old child His father took him to the hospital emergency room with complaints of urinating sparingly accompanied by complaints of always crying when urinating, complaints also accompanied by long duration of urination, sometimes dripping, the skin of the penis cannot be pulled back and the tip of the penis usually bulges with each urination. The patient was diagnosed with phimosis and managed by circumcision in the operating room. The patient's condition before the operation still had complaints such as when he was admitted and after the operation the patient's condition began to improve and the complaints were no longer there. Conclusion: Phimosis can be confirmed based on a guided history and correct and appropriate physical examination. The action that can be taken in cases of phimosis is circumcision surgery emergency. Abstrak. Fimosis adalah suatu kondisi di mana preputium tidak dapat diretraksi ke arah glans penis, sedangkan parafimosis adalah kondisi di mana preputium yang diretraksikan ke arah glans penis tidak dapat dikembalikan seperti semula. Terapi pembedahan pada fimosis dapat dilakukan dengan sirkumsisi. Pada kasus dengan komplikasi, seperti infeksi saluran kemih berulang atau balloning kulit preputium saat miksi, sirkumsisi harus segera dilakukan tanpa memperhitungkan usia pasien. Ilustrasi Kasus : Seorang anak berusia 6 bulan diantar oleh ayahnya ke IGD Rumah Sakit dengan keluhan buang air kecil sedikit-sedikit disertai keluhan selalu menangis saat buang air kecil, keluhan juga disertai dengan durasi buang air kecil yang lama, kadang menetes, kulit penis tidak dapat ditarik ke belakang dan ujung penis biasanya menggembung setiap buang air kecil. Pasien didiagnosis dengan fimosis dan ditatalaksana dengan melakukan tindakan sirkumsisi di kamar operasi. Kondisi pasien saat sebelum operasi masih ada keluhan seperti saat masuk dan setelah operasi keadaan pasien mulai membaik dan keluhan sudah tidak ada. Kesimpulan: Fimosis dapat ditegakkan berdasarkan anamnesis terpimpin dan pemeriksaan fisik yang benar dan tepat. Tindakan untuk kasus fimosis yang dapat dilakukan adalah tindakan bedah sirkumsisi emergensi.